The Relationship of Work Satisfaction with Nurse Commitments in the Organization of Hospital - Yusuf, Ah.; Christyana, Dina Septi; Has, Eka Mishbahatul M; Yunitasari, Esti (International Journal of Psychosocial Rehabilitation, 2020)
Nurses play an essential thing in patient caring because they are the first who deal with the patient. Patient satisfaction is a crucial concern in a hospital, so the nurses, who are at the forefront in meeting the demands of the patient, must have a certain level of organizational commitment and excellent job satisfaction. The researcher conducted this study to analyze the job satisfaction and corporate loyalty of nurses in the Premier Hospital of Surabaya and seek the correlation between that two variables. This study used a descriptive-analytic design with cross-sectional. Samples were a nurse at the hospital in Surabaya and were 132 respondents. The instrument used was the Job Descriptive Index, which modified to analyze job satisfaction and Allen and Meyer’s questionnaire to analyze organizational commitment. Analysis of the relationship between the two variables used the Spearman Rank Correlation analysis. The results showed that 88.6 % of respondents have moderate job satisfaction, 9.1 % have higher job satisfaction, and 2.3 % had low job satisfaction. While the organizational commitment of 97.7 % of respondents at a moderate level, 1.5 % at a weak level, and 0.8 % at stable levels. Analysis scored p=0.018. It means that there is a weak correlation between job satisfaction and organizational commitment. The conclusion that there is a weak correlation between job satisfaction and corporate loyalty of nurses in Premier Hospital of Surabaya. Further study should add more factors, which correlates with job satisfaction and organizational commitment.